Gambaran Motivasi Perawat Dalam Melakukan Dokumentasi Keperawatan Di Rsud Prof. Dr. Margono Soekarjo Purwokerto - Triyanto, Endang; Kamaluddin, Ridlwan (Jurnal Keperawatan Soedirman, 2008)
Nurse activity can be seen at nursing documentation result. It’s consist anamneses study, diagnose, planning, implementation and evaluation. Therefore nurse activity is one of quality service in hospital. This matter still need attention for nurse. The aim of this research was to know data motivate nurse to do nursing documentation in Prof. Dr. Margono Soekardjo Hospital of Purwokerto.Research study is survey with sectional cross. Research population is nurse take care of to lodge in RSUD Prof. Dr. Margono Soekardjo Hospital of Purwokerto. Technique of sampling with sampling purposive during 1 month. That consist minimize DIII nurse, one job experience year and ready to become responder, expected room head, installation head. Data taken to use containing question concerning factors influencing nurse motivation to do nursing documentation. Intrinsic factor concerning job quality determine quality of service of treatment, nurse express to agree ( 91%). To increasing functional nurse assessed from ability of nurse in nurse documentation, nurse express to agree ( 60%). Nurse documentation can be consideration to receive reward point, most nurses express to agree ( 62%). Statement concerning documentation will be more difficult with computerization system, 73 % nurse express disagree. Thereby can be concluded that 73 % nurse express to agree with the existence of documentation being based on computerization. The research conclusion was nurse express to agree with nursing documentation use computer system.